Pengembangan kompetensi guru dan peserta didik keahlian busana dalam mendesain busana digital dengan Ibis Paint X di SMK Sukapura Tasikmalaya - Cucu Ruhidawati; Mila Karmila; Katiah Katiah; Win Win Wiana; Asri Wibawa Sakti (Universitas Pendidikan Indonesia, 2024)
This community service activity is a follow-up to the mentoring program of the Center of Excellence Vocational School implemented at Sukapura Tasikmalaya Vocational School. The knowledge and skills of fashion design teachers in digital design still need strengthening and development. This condition is one of the bases for implementing community service by lecturers of the Fashion Design Education Study Program, FPTI UPI. Based on these conditions, the proposed community service program based on expertise in the field of science aims to realize a follow-up program from the results of the mentoring of the SMK Pusat Keunggulan (SMK PK) fashion expertise carried out by Lecturers of the Fashion Design Education Study Program, FPTI UPI. The impact of this program is expected to increase the ability of teachers and students with fashion expertise at SMK PK Sukapura Tasikmalaya to design clothes digitally using the